Chloramination of wastewater effluent: Toxicity and formation of disinfection byproducts - Le Roux, J.; Plewa, M.; Wagner, E.; Nihemaiti, M.; Dad, A.; Croue, Jean-Philippe (2017)
The reclamation and disinfection of waters impacted by human activities (e.g., wastewater effluent discharges) are of growing interest for various applications but has been associated with the formation of toxic nitrogenous disinfection byproducts (N-DBPs). Monochloramine used as an alternative disinfectant to chlorine can be an additional source of nitrogen in the formation of N-DBPs. Individual toxicity assays have been performed on many DBPs, but few studies have been conducted with complex mixtures such as wastewater effluents. In this work, we compared the cytotoxicity and genotoxicity of wastewater effluent organic matter (EfOM) before and after chloramination. The toxicity of chloraminated EfOM was significantly higher than the toxicity of raw EfOM, and the more hydrophobic fraction (HPO) isolated on XAD-8 resin was more toxic than the fraction isolated on XAD-4 resin. More DBPs were also isolated on the XAD-8 resin. N-DBPs (i.e., haloacetonitriles or haloacetamides) were responsible for the majority of the cytotoxicity estimated from DBP concentrations measured in the XAD-8 and XAD-4 fractions (99.4% and 78.5%, respectively). Measured DBPs accounted for minor proportions of total brominated and chlorinated products, which means that many unknown halogenated compounds were formed and can be responsible for a significant part of the toxicity. Other non-halogenated byproducts (e.g., nitrosamines) may contribute to the toxicity of chloraminated effluents as well.